PRIORITAS PENGEMBANGAN BISNIS AYAM KAMPUNG DENGAN MENGGUNAKAN METODE ANALISIS HIERARKI PROSES (AHP)(STUDI KASUS PERSEROAN TERBATAS (PT) SURYA PANGAN INDONESIA) - Rifaldi Gunawan; Jumiati; Nurdin (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
PT Surya Pangan Indonesia is one of Unismuh Makassar's business charities engaged in animal husbandry. The strategic location makes PT Surya Pangan Indonesia the farm of first choice for most consumers, restaurants, and other processed native chicken restaurants around Makassar City and Gowa Regency. However, the development of native chicken commodities is faced with various problems, namely both problems that occur in the internal environment and the external environment. The purpose of this study is to analyze the priority strategies that can be applied in developing the local chicken commodity business at PT Surya Pangan Indonesia. This research was conducted at the Kampung Chicken Farm of PT Surya Pangan Indonesia which is located in Pattallassang District, Gowa Regency. This research was conducted at PT Surya Pangan Indonesia Village Chicken Farm located in Pattallassang District, Gowa Regency. Informants in the study were 1 farm manager, 1 employee or Head of Cage, 1 trader (vendor), and 1 consumer or retailer. The data used are primary data and secondary data. The data analysis method used is AHP (Analytical Hierarchy Process) analysis, which is the Decision Stage to determine the priorities of several alternative strategies resulting from integration. the most important thing in AHP is pairwise comparison logic. The results showed that the priority strategy for developing the village chicken commodity business at PT Surya Pangan Indonesia farm is to optimize natural resources, human resources, and existing equipment resources with a value of 0.110. Keywords: Prioritization, business development, native chicken, hierarchical process analysis